Spatial Dimensions of Research on Alcohol and Sexual Risk: A Case Example from a Mumbai Study - Cromley, Ellen K. (2010)
Alcohol's role in unprotected sex is an important issue in the spread of HIV. Research on alcohol use in many countries has found complex relationships between individual characteristics, places where people drink, and consumption patterns. Data on drinking and leisure time activities and locations from in-person surveys with 1,239 young men aged 18–29 living in low-income communities in Mumbai, India, were analyzed. For every pair of men, an index of association measured the degree of similarity in their reported activities in specific communities. Multidimensional scaling of the similarity matrix revealed men who engaged in similar activities in the same communities. Hierarchical grouping classified men based on their activity dimensions. The ten groups of men, distinguished by their activities in particular communities, also differed in alcohol consumption, number of non-spousal sex partners, and level of unprotected sex. Understanding where activities take place is important in designing venue-based interventions to reduce health risk behaviors leading to the spread of HIV/AIDS.